Adjusted Survival Curves with Multivariable Laplace Regression. Issue 2 (March 2015) - Bellavia, Andrea; Bottai, Matteo; Discacciati, Andrea; Orsini, Nicola
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.